Postharvest storage of fresh spearmint as influenced by the application of spearmint essential oil and ascorbic acid - Xylia, Panayiota; Chrysargyris, Antonios; Christou, Christiana; Kotsoni, Andria; Gkretsi, Vasiliki; Tzortzakis, Nikos G. (My University, 2025)
Fresh culinary herbs are particularly perishable goods and thus their preservation is of great interest. Natural products such as essential oils (EO) and organic acids stands out as they are considered eco-friendly sanitizing and preservative agents. In the present work, spearmint EO and ascorbic acid (AA) assessed at different concentrations (EO: 0.01 and 0.1 %; AA: 0.5 and 1 %) and duration of application (1 and 5 min) on fresh spearmint quality characteristics at 4 °C for 6 d. High carvone levels were observed in EOs obtained from plants treated with AA (5 min), while a delay in carvone formation was observed in EOs from non-treated plants. The 1 min EO application decreased weight loss. Spearmint's sensory attributes (i.e. aroma and appearance) were not significantly affected by the treatments. The application of spearmint EO 0.01 %-1 min resulted in lower phenols, antioxidant activity, flavonoids and AA content suggesting a protective effect against oxidative stress that can accelerate the process of senescing. In addition, AA treatments decreased spearmint's total viable count, while both EO and AA treatments decreased yeasts and molds. Finally, prepared infusions and decoctions from spearmint following 6 days storage did not show any significant cytotoxic effect on either normal neuroglioma (H4 cells) or cancer cells (glioblastoma cells A172), while preparations from fresh spearmint (day 0) resulted in significant reduction in cell viability of A172 glioblastoma cells.
Keywords: Decoction; Infusion; Fresh herbs; Mentha spicata; Natural products; Quality